Existence results of fractional differential equations with nonlocal double-integral boundary conditions - Debao Yan (Mathematical Biosciences and Engineering, 2023)
This article presents the existence outcomes concerning a family of singular nonlinear differential equations containing Caputo's fractional derivatives with nonlocal double integral boundary conditions. According to the nature of Caputo's fractional calculus, the problem is converted into an equivalent integral equation, while two standard fixed theorems are employed to prove its uniqueness and existence results. An example is presented at the end of this paper to illustrate our obtained results.